Impact of Corona Crisis on European Climate Change Policy - Thomas M. Treptow (Wirtschaftsdienst)
Abstract The actual Corona crisis has a negative impact on the economic situation of the affected economies. This has direct consequences for the EU-wide trading of greenhouse gas emission allowances, which is an important building block of European climate change policy. In contrast, although there is an expected short-term decrease in the volume of greenhouse gas emissions due to the emerging economic recession, we should also expect lower prices of emission allowances in the mid to long term, which will make current production technologies more attractive. One important goal of European climate change policy — changing existing manufacturing technologies to less greenhouse gas emitting alternatives — will become even more difficult.